Pengembangan Antarmuka Portal Universitas untuk Meningkatkan Pengalaman Pengguna - Ikhwan Arief; Asmuliardi Muluk; Ahmad Syafruddin Indrapriyatna; Mahira Falevy (Ikatan Ahli Informatika Indonesia (IAII), 2021)
Technology has been growing rapidly to help humans living their everyday life. Human, as the user interacts through an interface called user interface (UI), and the experience that the users are having is called user experience (UX). UI and UX are inseparable as a good user interface will result in a better user experience. Portal Unand is a web-based app that has all academic information for students. An initial survey was conducted to find out student’s thoughts on Portal Unand. Students have complaints towards Portal Unand due to its unresponsiveness, old-fashioned design, important features weren’t highlighted, etc. Hence, it reduced user experience in using Portal Unand. In this study, the redesign was done by using the design thinking. The study started from empathizing with the users until testing the prototype to the users by conducting usability testing. Usability testing was conducted by using Maze and System Usability Scale (SUS). The score of usability testing was 84 which fell into the high range. The SUS score was 83.33 which fell into grade A and acceptable category. As the new prototype managed to fulfill users’ needs and met users’ expectations, the prototype was usable and ready to be developed.